Viewpoint of multi-omics potential in tuberculosis research: identifying biomarkers for biomanufacturing of efficient control tools - Otchere, Isaac Darko; Aboagye, Sammy Yaw; Arthur, Patrick Kobina; Asante-Poku, Adwoa (Frontiers in Tropical Diseases, 2024)
Tuberculosis (TB), caused by Mycobacterium tuberculosis complex (MTBC), remains a global health burden, claiming millions of lives annually. Despite the availability of a vaccine (the Bacillus Calmette-Guérin; BCG), diagnostics (smear microscopy and DNA-based diagnostics) and drugs for treatment, challenges like drug resistance, lower diagnostic sensitivity such as microscopy, instrumentation and high-level operational expertise requirement and poor vaccine efficacy pose a greater hinderance to TB monitoring and control. The inability of the BCG vaccine to protect against TB other than disseminated disease in neonates call for innovative approaches to provide improved interventions. This review highlights the potential of multi-omics as a powerful emerging tool offering a holistic insight into the intricate interplay between pathogens and the host immune response. It discusses the potential of multi-omics for discovering biomarkers as targets for rational drug design, production of more effective vaccines and as stable targets for production of universally applicable rapid diagnostics for early and accurate TB detection as well as monitoring treatment.